2018
DOI: 10.1186/s12904-018-0382-5
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating successful implementation of a person-centred intervention to support family carers within palliative care: a qualitative study of the Carer Support Needs Assessment Tool (CSNAT) intervention

Abstract: BackgroundAn understanding of how to implement person-centred interventions in palliative and end of life care is lacking, particularly for supporting family carers. To address this gap, we investigated components related to successful implementation of the Carer Support Needs Assessment Tool (CSNAT) intervention, a person-centred process of carer assessment and support, using Promoting Action on Research Implementation in Health Services (PARIHS) as a theoretical framework. This study identifies how the PARIH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…We have previously examined factors affecting the implementation of carer assessment and support more broadly within end-of-life care. 23 25 To better understand particular challenges encountered in this hospital context, we draw upon relevant aspects of the Nonadoption, Abandonment, Scale-up, Spread and Sustainability (NASSS) framework. 26 This framework suggests that sustaining implementation may be very difficult in contexts in which health conditions are unpredictable, where the intervention does not directly measure changes in health condition, and where the intervention does not readily align with prevailing organisation and system beliefs, including what counts as ‘high-quality’ evidence.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously examined factors affecting the implementation of carer assessment and support more broadly within end-of-life care. 23 25 To better understand particular challenges encountered in this hospital context, we draw upon relevant aspects of the Nonadoption, Abandonment, Scale-up, Spread and Sustainability (NASSS) framework. 26 This framework suggests that sustaining implementation may be very difficult in contexts in which health conditions are unpredictable, where the intervention does not directly measure changes in health condition, and where the intervention does not readily align with prevailing organisation and system beliefs, including what counts as ‘high-quality’ evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Having a CSNAT Champion within the team promotes and encourages team members to use the tool. Similarly, Diffin et al (2018b) found successful CSNAT implementation was associated with having internal facilitators within each team.…”
Section: Facilitators For Using the Csnatmentioning
confidence: 94%
“…They found that services with a higher proportion of internal CSNAT facilitators to staff members were more likely to be high adopters of the CSNAT, thus being more successful at implementing it. Diffin et al (2018b) found that the success of the implementation of the CSNAT was also determined by how the internal facilitator role was enacted within the service. The establishment of a team of internal facilitators, and giving them authority to manage the implementation process both positively influenced the success of CSNAT implementation.…”
Section: Shared Reviewmentioning
confidence: 99%
“…Another example of research exploring facilitation experiences includes a study in the UK that utilised interviews and field notes to examine the implementation of person-centred assessment and support in palliative care, using a model of internal and external facilitators, where all internal facilitators supported their local sites and the external facilitators provided monthly ‘peer support’ sessions to troubleshoot any barriers [ 11 ]. This study described how facilitation was crucial to motivating and supporting the use of the intervention within the specific context of implementation.…”
Section: Objectivementioning
confidence: 99%
“…A final example of previous research exploring facilitation experiences includes a doctoral thesis that explored facilitation within a neonatal intensive care unit [ 11 ]. In this research, facilitation was identified as crucial for bringing people together.…”
Section: Objectivementioning
confidence: 99%